The solid solution between platinum and palladium in nature - Bindi, L.; Zaccarini, F.; Garuti, G.; Angeli, N. [UNESP] (Mineralogical Society, 2013)
Chemical and structural data are reported for platinum-palladium intermediates from two nuggets found at Corrego Bom Sucesso, Minas Gerais, Brazil. Three grains with simple stoichiometries (i.e. PtxPd1 -x with x ∼0.67, ∼0.5 and ∼0.33, which correspond to Pt2Pd, PtPd and PtPd2, respectively) were characterized by single-crystal X-ray diffraction and electron-probe microanalysis. In the absence of single-crystal data it might be tempting to hypothesize that such simple stoichiometries represent distinct mineral species, however structural analyses show that all of the phases are cubic and crystallize in space group Fm3̄m. They are, therefore, natural intermediates in the palladium-platinum solid solution. Reflectance and micro-hardness values are reported for the samples and a comparison with the pure metallic elements made. On the basis of information gained from the chemical and structural characterization it can be concluded that there is a complete solid solution between Pt and Pd in nature. These findings corroborate results from experiments on synthetic compounds. © 2013 The Mineralogical Society.
Keywords: Alloys; Chemical composition; Palladium; Platinum; Unit-cell parameters; Chemical compositions; Minas Gerais , Brazil; Palladium-platinum; Platinum and palladiums; Single crystal x-ray diffraction; Structural characterization; Synthetic compounds; Alloying; Cerium alloys; Palladium alloys; Solid solutions; Stoichiometry; X ray diffraction; Platinum alloys; alloy; chemical composition; crystal structure; electron probe analysis; palladium; platinum; solid solution; stoichiometry; X-ray diffraction; Brazil; Minas Gerais